Randomized crossover trial to compare driving pressures in a closed‐loop and a conventional mechanical ventilation mode in pediatric patients. Issue 9 (22nd July 2021) - Ceylan, Gokhan; Topal, Sevgi; Atakul, Gulhan; Colak, Mustafa; Soydan, Ekin; Sandal, Ozlem; Sari, Ferhat; Ağın, Hasan
Abstract: Introduction: In mechanically ventilated patients, driving pressure (ΔP) represents the dynamic stress applied to the respiratory system and is related to ICU mortality. An evolution of the Adaptive Support Ventilation algorithm (ASV® 1.1) minimizes inspiratory pressure in addition to minimizing the work of breathing. We hypothesized that ASV 1.1 would result in lower ΔP than the ΔP measured in APV‐CMV (controlled mandatory ventilation with adaptive pressure ventilation) mode with physician‐tailored settings. The aim of this randomized crossover trial was therefore to compare ΔP in ASV 1.1 with ΔP in physician‐tailored APV‐CMV mode. Methods: Pediatric patients admitted to the PICU with heterogeneous‐lung disease were enrolled if they were ventilated invasively with no detectable respiratory effort, hemodynamic instability, or significant airway leak around the endotracheal tube. We compared two 60‐min periods of ventilation in APV‐CMV and ASV 1.1, which were determined by randomization and separated by 30‐min washout periods. Settings were adjusted to reach the same minute ventilation in both modes. ΔP was calculated as the difference between plateau pressure and total PEEP measured using end‐inspiratory and end‐expiratory occlusions, respectively. Results: There were 26 patients enrolled with a median age of 16 (9−25 [IQR]) months. The median ΔP for these patients was 10.4 (8.5−12.1 [IQR]) and 12.4 (10.5−15.3 [IQR]) cmH2O in the ASV 1.1 and APV‐CMV periods, respectively ( p < .001). The median tidal volume (VT) selected by the ASV 1.1 algorithm was 6.4 (5.1−7.3 [IQR]) ml/kg and RR was 41 (33 50 [IQR]) b/min, whereas the median of the same values for the APV‐CMV period was 7.9 (6.8−8.3 [IQR]) ml/kg and 31 (26−41[IQR]) b/min, respectively. In both ASV 1.1 and APV‐CMV modes, the highest ΔP was used to ventilate those patients with restrictive lung conditions at baseline. Conclusion: In this randomized crossover trial, ΔP in ASV 1.1 was lower compared to ΔP in physician‐tailored APV‐CMV mode in pediatric patients with different lung conditions. The use of ASV 1.1 may therefore result in continued, safe ventilation in a heterogeneous pediatric patient group.